DETERMINASI STUNTING:FAKTOR PENYEBAB DAN STRATEGI PENANGGULANGANNYA BERDASARKAN STUDI LITERATUR - Ananda Tri Agustiyani; Isnaini Nurul Jannah; Nazwa Alifa Abdurrahman; Afianti Sulastri; Agni Laili Perdani (LPPM UNIKAL, 2025)
In Indonesia, stunting remains a persistent public health problem.The purpose of this study was to systematically examine theunderlying causes of stunting. A review of previous studies onfactors influencing stunting in Indonesia was the methodologyused. The PRISMA diagram was used in the study selectionprocess to eliminate relevant studies. 16 studies out of 500 studieswere found to meet the requirements and were examined in moredetail.The study findings indicate that there are three main causesof stunting: (1) dietary and nutritional variables; (2) maternal andchild health factors; and (3) environmental and socioeconomic factors. Stunting is largely caused by inadequate food intake during first 1,000 days of life. The high rate of stunting in Indonesia is also influenced by the level of parental education,access to health facilities and sanitation, and maternal health conditions during pregnancy. These results are consistent with previous studies highlightthe importance a multifaceted approach in addressing stunting. Therefore, to reduce stunting rates in Indonesia, more coordinated policies are needed to improve maternal and child health care, increase access to nutrition, and empower the local economy